Crafting Algerian “Jben”: a traditional soft cheese enhanced by locally derived starters - BENDIMERAD, Nahida; BOUMEDIENE, Karima; KHIRI, Zahia; DIDOUH, Nassima; ANNTAR, Asmaa CHERIF; BENAMAR, Ibrahim; ZATLA, Ilyes; BOUDJEMAA, Boumediene MOUSSA (Food Science and Technology, 2024)
The global dairy industry faces challenges in sourcing cost-effective and suitable lactic starters for traditional cheese production. This study investigates the use of locally selected lactic starters in crafting Algerian Jben cheese, aiming to provide a sustainable alternative to imported starters. Local lactic starters comprising Lactococcus lactis, Leuconostoc mesenteroides, and Enterococcus durans were characterized by their technological properties when applied to cow's milk. The resulting cheese was compared with another cheese produced under similar conditions but using an industrial mesophilic starter, including strains of Lactococcus and Leuconostoc. Physicochemical and microbiological analyses were conducted on both cheeses, followed by sensory evaluations using the triangular and classification tests. Microbiological analyses revealed the absence of pathogenic germs or spores in both types of cheese. However, the cheese made with the industrial starter exceeded the standards for fecal coliforms and total coliforms. Titratable acidity measurements indicated comparable levels in both cheeses. Interestingly, there were no discernible differences in taste or aroma between the two types, with both being well received by tasters. In conclusion, our findings suggest that local lactic starters have the potential to replace the commercial starters currently employed in the Algerian dairy industry.